Pengaruh Media Tutup Botol Pintar terhadap Kemampuan Mengenalkan Huruf Hijaiyah di Kelompok B, TK Pelangi Harapan - Revalita S. Dos. Santos; Nurhayati Tine; Sri Rawanti (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
This study aims to determine the influence of the Smart Bottle Cap learning media on children's ability to recognize Hyaiyah letters. The research involved all students of Group B at Pelangi Harapan Kindergarten, using a total sampling technique due to the small population (fewer than 30 students). A total of 14 students were selected as the sample. Data were collected through observation and documentation, and analyzed using the t-test. The study was conducted at Pelangi Harapan Kindergarten, Kayubulan Village, Batudaa Pantai Subdistrict, Gorontalo Regency The results indicate that the use of the Smart Bottle Cap media significantly improves children's ability to recognize Hijaiyah letters. There was an increase in the mean score from 22.00 (pretest) to 32.21 (posttest). The combined t-test for the pretest and posttest showed a significanse value (sig) of 0.001 < 0.05, indicating a statistically significant influence therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.